A Study on the Plan for Child-Rearing-Friendly Housing: A Case Study on the Remodeled Public Housing in Kyoto, Japan - Hyunju Cho; Sangun Lee (Journal of Asian Architecture and Building Engineering, 2022)
In this study, we aimed to identify the planning conditions necessary for child-rearing-friendly housing by investigating an old municipal apartment in Kyoto City that was remodeled for achild-rearing household and determine the residents’ space utilization. The results were as follows: 1) Securing expandable space is highly beneficial for households with young children, especially when they utilize mostly the extended space for daily living. And asouth-facing arrangement is important to ensure comfort. 2) In plans for child-rearing households, it is necessary to secure enough storage space in consideration of the increase in the amount of necessary storage due to the children’s growth. 3) Restricted arrangement of household spaces to reduce movement is effective in supporting childcare. 4) It is desirable to design aspace to support residents so that they can utilize and modify it according to their needs, which change over time according to the age of their children.